Translation Reprogramming as a Novel Therapeutic Target in MAFLD. Issue 5 (3rd March 2022) - Metwally, Mayada; Berg, Thomas; Tsochatzis, Emmanuel A.; Eslam, Mohammed
Abstract: Approved pharmacotherapies for metabolic‐dysfunction‐associated fatty liver disease (MAFLD) are lacking. Novel approaches and therapeutic targets that are likely to translate to clinical benefit are required. Targeting components of the translation machinery hold promise as a novel therapeutic approach that can overcome the well‐known disease heterogeneity, as dysregulation of mRNA translation is a common feature independent of the MAFLD drivers. In this perspective, recent advances in understanding the role of mRNA translation in MAFLD are discussed, with a particular focus on the potential implications and challenges to "translate" these findings to the clinic, and an overview of similar recent efforts in other diseases is provided. Abstract : Novel approaches and therapeutic targets for metabolic‐dysfunction‐associated fatty liver disease (MAFLD) are required. In this perspective, recent advances in understanding the role of mRNA translation in MAFLD are discussed, with a particular focus on the potential implications and challenges to "translate" these findings to the clinic, and an overview of similar recent efforts in other diseases is provided.